CASC1 Expression in Bladder Cancer Is Regulated by Exosomal miRNA-150: A Comprehensive Pan-Cancer and Bioinformatics Study. (5th July 2022) - Luo, Huarong; Xu, Chengdang; Ge, Bujun; Wang, Tianru
Abstract : This study explored the role of cancer susceptibility 1 (CASC1) in tumorigenesis and development as well as the key pathways affecting bladder cancer progression. CASC1 was examined in various normal tissues in humans using the HPA database to quantify its expression level and subcellular localization. CASC1 is abundantly expressed in tumor tissues, primarily in cytoplasmic vesicles and stroma. TIMER2 was used to analyze the correlation between CASC1 expression levels and the types of infiltrates associated with immune cells and immunosuppressive cells. MDSC, Treg, M2, and CAF were significantly correlated with CASC1 expression in various tumors. Comparing patients with and without CASC1 mutation, those with CASC1 mutation had worse overall survival, progression-free survival, and disease-free survival. The correlation between has-miR-150 and CASC1 (for the case of bladder cancer) was then analyzed, and the related ceRNA network was mapped. A negative relationship between CASC1 expression and has-miR-150 expression was found in cases of bladder cancer. And the presence of miR-150-targeted CASC1 may be associated with bladder cancer progression. CASC1 is expressed at elevated levels in various tumor tissues, and it is associated with tumorigenesis and development. Exosomes containing miR-150-targeted CASC1 may affect the progression of bladder cancer.